2022
DOI: 10.3389/fimmu.2022.909315
|View full text |Cite
|
Sign up to set email alerts
|

Grass Carp Mex3A Promotes Ubiquitination and Degradation of RIG-I to Inhibit Innate Immune Response

Abstract: As one of the Mex3 family members, Mex3A is crucial in cell proliferation, migration, and apoptosis in mammals. In this study, a novel gene homologous to mammalian Mex3A (named CiMex3A, MW368974) was cloned and identified in grass carp, which is 1,521 bp in length encoding a putative polypeptide of 506 amino acids. In CIK cells, CiMex3A is upregulated after stimulation with LPS, Z-DNA, and especially with intracellular poly(I:C). CiMex3A overexpression reduces the expressions of IFN1, ISG15, and pro-inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…However, the effects of RIG-I therapy can be influenced by numerous factors. Previous studies identified a negative correlation between RIG-I and MEX3A in tumorigenesis 47 , 49 . MEX3A, an RNA-binding protein (RBP), post-transcriptionally regulates a number of biological processes, including tumor immunologically relevant ones, thereby, leading to the immune evasion of tumor cells.…”
Section: Discussionmentioning
confidence: 84%
“…However, the effects of RIG-I therapy can be influenced by numerous factors. Previous studies identified a negative correlation between RIG-I and MEX3A in tumorigenesis 47 , 49 . MEX3A, an RNA-binding protein (RBP), post-transcriptionally regulates a number of biological processes, including tumor immunologically relevant ones, thereby, leading to the immune evasion of tumor cells.…”
Section: Discussionmentioning
confidence: 84%
“…The rapid upregulation of IL-1β and TNFα mRNA expression in the APS–Vaccine group suggests that the treatment could more effectively mitigate the inflammatory response. IFN1 plays a crucial role in the host’s defense against viruses, and a significant increase in its mRNA expression levels was observed in the kidney after vaccination [ 50 , 51 ]. In our research, we noticed an upregulated trend at various time points for the mRNA expression of IFN1 and IFN-γ2 in the APS–Vaccine group, which illustrates the effective improvement in both cellular and humoral immunity to defend against GCRV infection in grass carp.…”
Section: Discussionmentioning
confidence: 99%
“…The RING domain is the critical functional domain for RING finger family E3 ubiquitin ligases. Truncation mutation within RING domain abolished the ability of Mex3A to induce the ubiquitination and degradation of RIG-I [28]. TRIM40 mutant lacking RING domain greatly impaired its inhibition on IFN-b promoter activity [5].…”
Section: Discussionmentioning
confidence: 99%